2021
DOI: 10.31237/osf.io/wzjdf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

English for Informatics Engineering

Abstract: Dalam perkembangannya, bahasa Inggris telah menjadi salah satu bahasa utama di berbagai konteks kehidupan, baik itu formal maupun informal, lisan maupun tulisan, interpersonal maupun transaksional. Hal ini mendorong dunia pendidikan untuk mengembangkan pembelajaran Bahasa Inggris baik sebagai disiplin ilmu maupun sebagai media untuk belajar keilmuan lainnya. Bahasa Inggris sebagai disiplin ilmu mencakup ilmu linguistik maupun budaya. Adapun bahasa Inggris sebagai media belajar ditujukan untuk memperdalam pemah… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The podcast offered incredible subject matter and learning exercises that helped teachers and students alike broaden their horizons and improve their English communication abilities. The outcomes of the search revealed that incorporating listening strategies into a listening lesson through a cycle of actions as movements in guided metacognitive succession, such as a pre-listening activity, first listen, and pair processbased discussion using materials sources from podcasts, was successful and enhanced the students' listening skills (Sukmawati, 2021). Their pre-test, post-test I, and post-test II results were all significantly higher on average.…”
Section: Introductionmentioning
confidence: 99%
“…The podcast offered incredible subject matter and learning exercises that helped teachers and students alike broaden their horizons and improve their English communication abilities. The outcomes of the search revealed that incorporating listening strategies into a listening lesson through a cycle of actions as movements in guided metacognitive succession, such as a pre-listening activity, first listen, and pair processbased discussion using materials sources from podcasts, was successful and enhanced the students' listening skills (Sukmawati, 2021). Their pre-test, post-test I, and post-test II results were all significantly higher on average.…”
Section: Introductionmentioning
confidence: 99%